Proinflammatory dietary intake is associated with increased risk of colorectal cancer: Results of a case-control study in Argentina using a multilevel modeling approach - Niclis, Camila (2018)
Little evidence regarding the inflammatory potential of diet and its effect on colorectal cancer exists in Latin American countries. The aim of the present study was to evaluate the association between the Dietary Inflammatory Index (DII®) and colorectal cancer (CRC) risk in Córdoba, Argentina. A frequency-matched case-control study (N D 446, including 144 (32.3%) CRC cases and 302 (67.7%) controls was conducted in Córdoba (Argentina) from 2008 through 2015. DII° scores were computed based on dietary intake assessed by a validated food frequency questionnaire (FFQ). Multilevel logistic regression models were fit to evaluate the association between DII scores and CRC, following adjustment for age, body mass index, sex, energy intake, smoking habits, socio-economic status, physical activity, and use of nonsteroidal anti-inflammatory drugs as first-level covariates and level of urbanization as the contextual variable. Odds of colorectal cancer increased linearly with increasing DII scores (ORcontinuous 1.34; 95%CI 1.07 to 1.69 and ORtertile3 vs. tertile1 1.21; 95%CI 1.01 to 1.44). The association was stronger among men than women (ORcontinuous 1.29; 95%CI 1.21 to 1.37 vs. ORcontinuous 1.05; 95%CI 0.83 to 1.33, respectively). A proinflammatory diet, reflected by higher DII scores, was positively associated with colorectal cancer occurrence, mainly in men.